Foreign experience of public administration in emergency situations - Kashchenko , Dmytro (Pressing Problems of Public Administration, 2024)
The article examines international practices in public administration during emergencies, with a focus on adapting them to Ukraine’s specific realities. The relevance of this topic is highlighted in the context of increasing natural, technological, and humanitarian crises, which demand effective performance from public institutions. Special attention is given to the challenges posed by Russia’s full-scale aggression against Ukraine, accompanied by widespread destruction and socio-economic crises. The article reviews best practices in public administration during emergencies implemented in countries such as the United States, Germany, Japan, the United Kingdom, Israel, Canada, and Australia. Key elements of their crisis management models are identified, including: a multi-level institutional structure with clearly defined powers; legal frameworks for crisis management based on overarching laws and action plans; advanced communication strategies to ensure timely public information dissemination; the use of innovative technologies such as geographic information systems, artificial intelligence, and drones; and active collaboration between government agencies, local authorities, civil society organizations, and the private sector. The analysis concludes that effective crisis management integrates centralized strategic leadership with broad autonomy for regional and local authorities. Particular emphasis is placed on Israel’s experience, especially its strategic communication models, the involvement of volunteer organizations, and the practice of preparing citizens for military-related emergencies. The necessity of implementing a national early warning system, developing situational centers, and digitizing management processes in Ukraine, particularly for emergency forecasting, is underscored. Specific recommendations are provided for improving the legislative framework, enhancing institutional capacity, adopting modern technologies, and developing effective communication strategies. The paper outlines prospects for further research aimed at incorporating international experience into Ukraine’s legal and administrative framework and formulating practical recommendations to optimize the functioning of public authorities and local governments during crises.